EKSISTENSI HUKUM PIDANA ADAT DI INDONESIA : Pengkajian Asas, Norma, Teori, Praktik dan Prosedurnya - Mulyadi, Lilik (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2013)
Existence of indigenous Indonesian criminal law examined from the perspective of normative (ius constitutum) set forth in Article 18 B of the 1945 Amendment, Article 1, Article 5 paragraph (3) sub B Drt Law No. 1 of 1951, Article 5 paragraph (1), Article 10 paragraph (1) and Article 50 paragraph (1) of Law No. 48 of 2009. Then partial in certain areas such as Nanggroe Aceh Darussalam stipulated in Law No. 44 of 1999, Act No. 11 of 2006, the next is implemented in the form of Qanun both provincial and district levels. Next in Bali set up and implemented in the form of Awig - Awig Village People (Pakraman) as well as from the perspective of ius constituendum set out in Article 2 paragraph (1), (2) of the RUU KUHP of 2012. Then the level of principle set Ciwasasana book or book Purwadhigama, Book of Gajah Mada, Simbur Cahaya, Book Kuntara Raja Niti, Book Lontara 'ade' and Awig awig. In addition, examined from the perspective of theory, practice and procedures found in the form jurisprudence Mahkamah Agung RI as Putusan Mahkamah Agung RI No. 42 K/Kr/1966 Tanggal 8 Januari 1966, Putusan Mahkamah Agung RI No. 275 K/Pid/1983 tanggal 29 Desember 1983 and sanctions adat (traditional medicine) for recovery of the balance essentially magical nature, the cosmos recovery to restore the disturbed balance in order to be religio magic back. Later in the study of criminal law the existence of indigenous Indonesian criminal law is at the level of dogmatic law, legal theory and philosophy of law. Therefore customary criminal law holistically animates all levels of law in the practice of law so that the existence of the law - dimensional nature of criminal law is undoubtedly indigenous capabilities as a characteristic practice of law in Indonesia. Keywords: criminal law customary, traditional sanctions, as well as the principles,Â norms, theories, practices and procedures